Szlifowanie Powierzchni Płaskich za Pomocą Tarcz Ściernych - Ripianu, A.; Tudosie, C. (Engineering Transactions, 1963)
A cylindrical abrasive disc is considered in the process of grinding a plane surface by means of its end surface constituting a circular ring. The abrasive disc rotates about its geometric axis which is fixed in general. The ground object performs a rectilinear or rotatory motion about axis parallel to the axis of the disc. The disc performs also direction if the ground surface forms a translational motion, in the vertical a recess. Three diffesent cases are considered.1) The disc rotates about its symmetry axis. with angular velocity w and the ground object moves rectilinearly with velocity vo. 2) The disc rotates about its symmetry axis with angular velocity w, and the object rotates with a fixed axis parallel to that of rotation of the disc. angular velocity w1 about a fixed. 3) The disc rotates about its symmetry axis with angular velocity w and this axis moves along ground objects moves rectilinearly with velocity vo. a circular path with angular velocity w1. The ground objects In these cases the problem of power consumption is solved for the grinding process. Relations between the speed of the disc and that of the work are derived for minimum power consumption.